La defensoría comunitaria y su rol en el cumplimiento de los derechos a mujeres víctimas de violencia de la parroquia 7 de julio, en la actualidad - Encalada Proaño, Sara Graciela (2024)
This research on the role of community advocacy in the prevention and comprehensive care of violence against women in the parish of 7 de Julio. The study is framed in a socio-critical paradigm, the specific objectives included identifying the activities of the ombudsman's office, examining procedures and limitations, and proposing an intervention to strengthen its work. A methodology with a mixed approach was used, with quantitative and qualitative techniques, that is, focus groups were held to explore the experiences of women in the ombudsman's office and surveys were applied to officials of the cantonal council for the protection of rights to examine the procedures and limitations. The most relevant percentages of the results of the research are reflected in the positive opinion of the activities of the ombudsman's office by the officials of the cantonal council for the protection of rights, with 85% approval. This research has allowed us to learn about the current situation of the community ombudsman's office of the parish of 7 de Julio and the cantonal council for the protection of rights, there is an outstanding difference of opinion between the community ombudsmen and the officials, as well as the importance of establishing mechanisms and strategies that promote effective communication to position the community ombudsmen as a mechanism for primary attention in cases of rights violations. Through the proposed intervention, the capacities of the ombudsman's office can be strengthened to improve the response and protection of victims of violence and the defense of the rights of the citizens of the Shushufindi canton.